Gender-specific cut-offs in colorectal cancer screening with FIT: Increased compliance and equal positivity rate. (June 2019) - Blom, Johannes; Löwbeer, Christian; Elfström, K. Miriam; Sventelius, Marika; Öhman, Daniel; Saraste, Deborah; Törnberg, Sven
Objective: Using quantitative Faecal Immunochemical Test (FIT) in colorectal cancer screening enables adjustment of the cut-off for a positive test. As men have higher stool blood levels and higher prevalence of colorectal neoplasia, different cut-off levels can be chosen for men and women. We evaluated participation and positivity rates switching from guaiac-based faecal occult blood test (gFOBT) (Hemoccult®) to FIT (OC-Sensor), using gender-specific cut-offs. Methods: The colorectal cancer screening programme of Stockholm-Gotland, Sweden, started in 2008 and invited individuals aged 60–69 to biennial testing using gFOBT. From 1 October 2015 the test was switched to FIT, with positivity cut-offs of 40 (200) and 80 (400) µg Hb/g (ng/mL) faeces for women and men, respectively. The first year was evaluated for compliance and positivity, number of reminders and incorrect/inadequate tests, compared with gFOBT in the preceding 12-month period. Results: There were 127, 030 and 87, 269 individuals invited to screening with gFOBT and FIT, respectively. The change of test increased overall participation by 11.9% (95% confidence interval 11.5%–12.3%) from 56.5% to 68.4% ( p < 0.001). The increase was larger in men (14.3%) than women (9.7%), and in those aged 60–64 (14.2%) than those aged 65–69 (8.7%). The positivity rate was 2.6% in women and 2.5% in men. There was a lower rate of reminders and incorrect/inadequate tests with FIT. Conclusions: Within a well-organised colorectal cancer screening programme, changing the test from gFOBT to FIT markedly increased participation, especially among men, and in the younger age group. With a lower cut-off in women than men, the positivity rate was similar.